SCREENING OF SOUTH INDIAN HERBS FOR QUORUM QUENCHING PROPERTY. - ANITHA.K; MAHALAKSHMI.T (International Journal of Pharma and Bio Sciences, 2012)
All bacteria communicates by a process called Quorum sensing. In which the bacteria secrete small molecules are called auto inducer that acts a molecular “Messenger”, the auto induces increase with increase in bacterial population and are able to involve in Quorum sensing only after reaching a threshold. Concentration anti quorum sensing agents. Would offer ofcontrolling microbial infection with advantages of reducing risk of resistance development. The continuing search for new and novel anti microbials and anti pathogenic agents has focused on exploiting the fact that plants serving in an environment with high bacterial density has been seen to posses productive means against infection. Naturalproducts especially south Indian folk plants shows the promising results in curing of diseases and bacterial infections in this study 15 plants were investigated and all the plants shows the activity in which Termanalia chebula was found to be a leading plants followed by awsonia inermis, solanum torvum, termanalia arjuna.